Recent outcomes of the extracardiac Fontan procedure in patients with hypoplastic left heart syndrome - Alisa Arunamata; Theresa A Tacy; Saraswati Kache; Richard D Mainwaring; Michael Ma; Katsuhide Maeda; Rajesh Punn (Wolters Kluwer Medknow Publications, 2020)
Objective: To investigate patient-related factors, echocardiographic, and anatomic variables associated with immediate and long-term clinical outcomes after extracardiac Fontan procedure at our institution. Materials and Methods: Retrospective review of preoperative cardiac catheterizations and echocardiograms as well as medical records of all children with hypoplastic left heart syndrome (HLHS) who underwent Fontan between June 2002 and December 2018. Results: Seventy-seven patients with HLHS were included (age 4 years [1.5-11.7]). Seventy patients (91%) received a nonfenestrated Fontan and 57 patients (74%) underwent Fontan without cardiopulmonary bypass (CPB). Presence of a Fontan fenestration (P = 0.69) and use of CPB (P = 0.79) did not differ between those with <2 weeks compared to those with =2 weeks of chest tube drainage. There were no differences in either pre- or intra-operative hemodynamics between patients who weighed <15 kg compared to those who weighed ≥15 kg at time of surgery; incidence of death, transplant, and transplant listing were similar between weight groups. Inferior vena cava (IVC) diameter z-score did not differ among patients with and without chylous chest tube drainage (P = 0.78), with and without development of protein losing enteropathy (P = 0.23), or death/heart transplant/transplant listing compared to survivors without transplant (P = 0.26) Conclusion: In HLHS patients undergoing Fontan, preoperative weight and IVC diameter appeared to have no influence on immediate postoperative outcomes. Performing the Fontan off CPB and with a fenestration also conferred no added clinical benefit. These observations should be considered when deciding optimal timing for Fontan completion.